Prospects for the use of pumice from Georgia in lightweight concretes - G. P. Tsintskaladze; T. N. Kordzakhia; T. V. Sharashenidze; M. G. Zautashvili; G. M. Beridze; V. M. Gabunia; I. R. Javakhishvili (Хімія, фізика та технологія поверхні, 2024)
Lightweight concrete is a building material with a density not exceeding 2000 kg/m3. Its structure is determined by the structure of the used components and manufacturing methods. The advantages of these building materials are their low density, good thermal insulation, frost resistance, high thermal resistance, ease of use of blocks, which is due to their large size and low weight; also important is their wide range, which allows one to choose the optimal material composition suitable for operating conditions.